Effect of Fish Collagen Hydrolysates on Type I Collagen mRNA Levels of Human Dermal Fibroblast Culture - Ana Sanchez; Maria Blanco; Begoña Correa; Ricardo I. Perez-Martin; Carmen G. Sotelo (Marine Drugs, 2018)
Fish discards and subproducts may represent an important source of raw material, not only for the food industry, but for other different kind of industries, such as the nutraceutical and cosmetic industries. Collagen, which is mainly obtained from animal skins, is an important structural protein in the animal kingdom having many different applications. It is well known that fish skins constitute a significant subproduct in the fishery industry, especially in the case of some species, where fish skins may represent up to 20% of the total body weight of fish. Peptides from collagen hydrolysates have been described to be useful for preventing skin aging and osteoarthritis, however, the mechanism for these biological activities is not well known. Fibroblasts are the main cell types involved in the collagen synthesis, and in the present work, human dermal fibroblasts have been exposed to the treatment of collagen peptides of two different molecular weight ranges. Results show that higher molecular weight collagen peptides produce higher synthesis of collagen type I mRNA and, therefore, it may suggest that prior molecular weight selection may be an important step to maximize the effect of collagen hydrolysates on collagen type I synthesis by dermal fibroblasts.